Влияние предварительной деформации зубных титановых имплантатов на их коррозионные свойства в среде полости рта - Лавренко, В.А.; Гогаев, К.А.; Талаш, В.Н.; Лось, В.В.; Руденко, Ю.Б.; Бошицкий, К.Ю. (Доповіді НАН України, 2010)
За допомогою методiв потенцiодинамiчних анодних поляризацiйних кривих та хiмiчного аналiзу iонiв титану рiзної валентностi у розчинi на рiзних етапах електролiзу визначений вплив деформацiї (ступеню стиску при волочiннi титанового дроту через фiл’єри з кiнцевим зменшенням дiаметра вiд 3 до 40%) на швидкiсть взаємодiї з електролiтом (3%-ний розчин NaCl) та на формування захисних оксидних плiвок Ti2O3 i TiO2. Показано, що найбiльший опiр корозiї мають титановi дроти зi ступенем деформацiї 3–10%, який вiдповiдає значному змiцненню iмплантату. The influence of a deformation (crimping grade) at the broaching of a titanium wire through the drawing nozzles for a final decrease of the wire diameter in the range of 3. . . 40% on the rate of interaction with electrolyte (3% NaCl solution) and formation of Ti2O3 and TiO2 protective oxide films has been investigated using the anodic polarization curves method as well as the chemical analysis of titanium ions of different valences in the solution for different stages of electrolysis. It has been shown that titanium wires with the deformation grade of 3. . . 10% promoting the essential strengthening of the implant are characterized by the highest corrosion resistance.